Nuclear actin polymerization rapidly mediates replication fork remodeling upon stress by limiting PrimPol activity - Palumbieri, Maria Dilia; Merigliano, Chiara; González-Acosta, Daniel; Kuster, Danina; Krietsch, Jana; Stoy, Henriette; von Känel, Thomas; Ulferts, Svenja; Welter, Bettina; Frey, Joël; Doerdelmann, Cyril; Sanchi, Andrea; et al. (Nature communications, 2023)
Cells rapidly respond to replication stress actively slowing fork progression and inducing fork reversal. How replication fork plasticity is achieved in the context of nuclear organization is currently unknown. Using nuclear actin probes in living and fixed cells, we visualized nuclear actin filaments in unperturbed S phase and observed their rapid extension in number and length upon genotoxic treatments, frequently taking contact with replication factories. Chemically or genetically impairing nuclear actin polymerization shortly before these treatments prevents active fork slowing and abolishes fork reversal. Defective fork remodeling is linked to deregulated chromatin loading of PrimPol, which promotes unrestrained and discontinuous DNA synthesis and limits the recruitment of RAD51 and SMARCAL1 to nascent DNA. Moreover, defective nuclear actin polymerization upon mild replication interference induces chromosomal instability in a PRIMPOL-dependent manner. Hence, by limiting PrimPol activity, nuclear F-actin orchestrates replication fork plasticity and is a key molecular determinant in the rapid cellular response to genotoxic treatments. How nuclear architecture assists the replication stress response is still largely unknown. Here the authors show that nuclear actin polymerization rapidly extends upon mild DNA damage. By limiting Primpol activity, this response mediates fork slowing and reversal, protecting chromosome stability.